Modelling Dynamic Impact of Governance and External Shocks on Fiscal Performance in Indonesia - Mansur Muhammad; Herbert Wibert Victor Hasudungan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
The purpose of this study is to empirically investigate the impact of external shocks and good governance on fiscal performance in Indonesia. Data for this study, covering the period from 2002 to 2021, was collected from reputable sources such as the International Monetary Fund, World Bank, and World Governance Indicators. To conduct a rigorous analysis, we employed robust generalized method of moments (GMM) techniques to examine the data. Prior to estimation, several preliminary analyses were conducted to ensure the reliability of the results. They include descriptive analysis, principal component analysis was conducted to reduce the dimensionality of governance indicators, and unit root test. This study empirically found that oil price shocks have a negative effect on fiscal performance, reflecting the profound influence of these shocks on various sectors of the economy. Additionally, the study confirms the positive relationship between good governance and fiscal performance, emphasizing the role of governance as a driver of efficient resource allocation and development, not only in Indonesia but also in other economies. Findings emanating from this study underscore the significance of considering good governance and external shocks when formulating fiscal policies and strategies for sustainable economic growth and development.